Understanding the boom: Country study - Tanzania - Mark Henstridge (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
There are large volumes of gas offshore Tanzania, which has raised hopes of a boom. But those hopes look set to be disappointed. A boom would depend on there being a sizeable flow of revenue to government from producing and exporting gas. This paper sets out the scale of the gas, and the array of risks which currently make investment in gas production, and any associated boom, unlikely. As well as geological, engineering, and market risks, the risks to investment from public policy have been elevated over the last few years.
Keywords: O11; O13; O43; Q32; Q33; Q35; 330; developing countries; economic development; institutions and economic growth; non-renewable natural resources; macroeconomics